Population genomics and gene introgression in goat herds naturally adapted to Brazil - Moura, Jeane; Campelo, José Elivalto; Bajay, Miklos; Sarmento, José Lindenberg; Araújo, Adriana (Revista Ciência Agronômica, 2019)
The aim of this study was to apply the Illumina 50 K goat SNP Chip to analyse population genomic structure in two herds of Marota goats in the State of Piauí, one private and the other an official conservation herd, and to investigate evidence of genetic erosion in these herds caused by the Anglo-Nubian goat. To that end, 86 Marota and 10 Anglo-Nubian animals were genotyped. Genetic diversity was analysed by comparing minor allele frequency (MAF) in the herds. Population structure and genetic differentiation were evaluated using a Bayesian approach, principal component analysis (PCA) and the fixation index (FST). High genetic differentiation (FST = 0.16) was seen in the Marota population in relation to the Anglo-Nubian. The private herd shared a greater number of fixed SNPs with the herd of Anglo-Nubians (1024) than did the conservation herd (741). The results of the PCA, together with those from the analysis carried out using the Structure software, showed the presence of Anglo-Nubian genes in the Marota herds. It can therefore be concluded that the high level of polymorphism and high genetic differentiation between Marota and Anglo-Nubian goats characterise these animals as a source of genetic diversity for goat farming in the region; the Illumina 50 K goat SNP Chip is efficient in population structure analysis in Marota goats; microarray technology, analysis using the Structure software, and Principal Component Analysis complement each other in expanding the ability to detect gene introgression in small populations; there is evidence of the introgression of Anglo-Nubian genes in the herds of Marota goats under analysis.